THE MATRIX OF COMPETENCIES AS A TOOL OF ENTREPRENEURSHIP BACHELOR EDUCATION - Yu. B. RUBIN; M. V. LEDNEV; D. P. MOZHZHUKHIN (Высшее образование в России)
The article reviews the matrix of competencies use for studying and formation of educational programs in entrepreneurship at bachelor’s degree. The authors examine the problem of standardization in the field of entrepreneurship education in the context of unification and harmonization of approaches to teaching entrepreneurship at universities. Since there are no special state educational standards in the sphere of entrepreneurship education, the universities have to work out their own educational programs within such fields of study as ‘Management’, ‘Economics’, ‘Business Informatics’, ‘Innovation Studies’, ‘Tourism’, ‘Trade Business’, ‘Hotel Industry’, and even ‘Metallurgy’. The paper critically views the matrix of entrepreneurial competencies worked out on the basis of Federal State Educational Standard for Bachelors in Management and analyzes the limitations and shortcomings of this approach. Special attention is paid to the competitive competencies which the authors attribute to the professional module.